(18F)-Fluorodeoxyglucose positron emission tomography/magnetic resonance imaging assessment of hypometabolism patterns in clinical phenotypes of suspected corticobasal degeneration - Franceschi, Ana; Clifton, Michael; Naser-Tavakolian, Kiyon; Ahmed, Osama; Cruciata, Giuseppe; Bangiyev, Lev; Clouston, Sean; Franceschi, Dinko (World Journal of Nuclear Medicine, 2021)
Corticobasal degeneration (CBD) is a rare neurodegenerative disorder presenting with atypical parkinsonian symptoms that characteristically involves the frontoparietal region including the primary sensorimotor cortex, ipsilateral basal ganglia, and thalamus, typically in an asymmetric pattern. We aim to evaluate the metabolic and volumetric abnormalities in patients with clinically suspected CBD phenotypes utilizing hybrid 18F-fluorodeoxyglucose (FDG) positron emission tomography–magnetic resonance (PET/MR) brain imaging. A retrospective analysis was performed on 75 patients (mean age 74 years, 31 males and 44 females) who underwent 18F-FDG PET/MR imaging (MRI) as part of their clinical dementia workup. Images were obtained using an integrated Siemens mMR 3T PET/MRI scanner. Two board-certified neuroradiologists and a nuclear medicine physician evaluated the metabolic and volumetric data of each hemisphere to assess for symmetric or asymmetric involvement of regions of interest in the subset of patients with suspected CBD. Of the 75 patients, 12 were diagnosed with suspected CBD based on a combination of clinical symptoms, neurocognitive testing, and hybrid neuroimaging findings. Ten of 12 patients (87%) demonstrated asymmetrically decreased FDG uptake involving a single cerebral hemisphere and ipsilateral subcortical structures, whereas two of 12 patients (13%) demonstrated striking hypometabolism of the bilateral sensorimotor cortices. Our study highlights two characteristic patterns of hypometabolism in patients with clinical and neuroimaging findings suggestive of the underlying CBD. The first pattern is asymmetric hypometabolism and volume loss, particularly within the frontoparietal and occipital cortices with involvement of ipsilateral subcortical structures, including the basal ganglia and thalamus. The second, more atypical pattern, is symmetric hypometabolism with striking involvement of the bilateral sensorimotor cortices.
Keywords: Corticobasal degeneration; fluorodeoxyglucose; hybrid neuroimaging; positron emission tomography; magnetic resonance imaging